PENGARUH KECERDASAN EMOSI TERHADAP KECEMASAN MENGHADAPI ULANGAN AKHIR SEMESTER PADA SISWA KELAS X SMK NEGERI 3 YOGYAKARTA [CORRELATION BETWEEN EMOTIONAL INTELLIGENCE WITH ANXIETY ON PREPARING FINAL SEMESTER EXAM FOR TENTH GRADE STUDENTS OF VOCATIONAL HIGH SCHOOL 3 YOGYAKARTA] - Perdana, Fauzi Satria; Bhakti, Caraka Putra; Iriastuti, Mae Endang (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2022)
This research aims to examine the influence of emotional intelligence on anxiety facing the Final Semester Examination in Class X students at SMK Negeri 3 Yogyakarta. This research is correlational research using a quantitative approach. The research sampling technique used random sampling technique. Data collection instruments used an emotional intelligence level scale and an anxiety scale for facing end-of-semester exams. This research concludes that there is a significant relationship between the level of emotional intelligence and the level of anxiety facing the final semester exams in class X students at SMK Negeri 3 Yogyakarta. The correlation coefficient value is -0.447 and the determination coefficient is 0.200.